Neck recurrence in papillary thyroid carcinoma - DEDIVITIS,ROGÉRIO APARECIDO (2020)
ABSTRACT Introduction: papillary thyroid carcinoma is a tumor with good prognosis. However, some patients treated present neck recurrence. Objective: to evaluate the risk factors for neck recurrence. Methods: a retrospective study enrolled 89 patients (68 women and 21 men) diagnosed with papillary carcinoma who underwent total thyroidectomy. In 21 patients, neck dissection was performed and 62 patients underwent radioiodinetherapy. Twelve patients relapsed with metastasis in this period with an average of 3.6 years. Results: out of 89 patients, 76.4% were female. Relapse occurred in nine (13.23%) women and three (14.28%) men. The average age of the patients was 44 years in the control group and in patients with relapsed. Eighteen patients (23.37%) in the control group and eight (64.28%) who relapsed had positive lymph nodes at initial diagnosis. The tumor size was significantly larger in the group of patients with cervical recurrence (3.3cm vs. 1.6cm - p=0.008, Student t test), whereas the presence of metastatic lymph nodes at the moment of the first operation was also significant (p=0.004 -Fisher exact test). The tumor size was an independent risk factor for recurrence at the multivariate anaylsis (OR=2.4, IC95%:1.3-4.6 - p=0,007, logistic regression). Conclusion: there is an increase in the risk of lymph node recurrence during the follow up of 2.4 folds for each increase of 1cm in the longer nodule diameter.